Addressing Multi-Unit Residential Management Conflicts: A Legal Study: Mengatasi Konflik Pengelolaan Hunian Multi-Unit: Sebuah Studi Hukum - Patanroi, Berlinaldo (Universitas Muhammadiyah Sidoarjo, 2023)
This study delves into the legal complexities and challenges arising from the management dualism disputes within the Association of Occupants and Owners of Flat Units (P3SRS) at the Bogor Valley Apartment. The research adopts a normative juridical approach, focusing on the analysis of primary, secondary, and tertiary legal materials through comprehensive library research. Central to this investigation is the exploration of the authority of P3SRS under Article 27 of the Regulation of the Minister of PUPR Number 14 of 2021. The study reveals that the existing dual administrations within the P3SRS lack the legitimate authority to manage the interests of the apartment's owners and residents as stipulated by the regulation. This situation has led to significant legal issues, primarily triggered by the dismissal and replacement of P3SRS management. The research further examines legal protection mechanisms for residents and owners affected by this dualism, highlighting two primary approaches: 'preventive legal protection' through government-led socialization and awareness campaigns, and 'repressive legal protection' as outlined in existing housing laws and regulations. Additionally, the study discusses the role of the independent Notary Honor Council (MKN) in providing legal protection for notaries concerning their civil responsibilities and the creation of legal documents. The findings underscore the necessity for clear regulatory frameworks and effective legal protection strategies to address and mitigate the challenges posed by management dualism in residential unit associations, providing valuable insights for policymakers, legal practitioners, and residents of multi-unit dwellings.Highlights: The study identifies illegal authority in dual residential management structures, highlighting a lack of legitimate power in handling owner and resident interests. It emphasizes the necessity of preventive legal protection, advocating for government-led awareness initiatives to educate communities about residential management laws. The research underscores the importance of repressive legal measures, detailing how existing housing regulations provide protection against management conflicts. Keywords: Residential Management, Legal Dualism, Preventive Protection, Repressive Protection, Regulatory Framework